2018
DOI: 10.1002/cjoc.201700805
|View full text |Cite
|
Sign up to set email alerts
|

Lactonization of C(sp2)—H Bonds in Enamides with CO2

Abstract: Herein, we report a novel synthesis of 1,3-oxazin-6-ones from enamides with CO 2 through C-H carboxylation and one-pot cyclization. This transition-metal-free and redox-neutral process features broad substrate scope, good functional group tolerance and facile product derivatization. The nucleophilic attack to CO 2 from the electron-rich alkene is demonstrated for this reaction.At the beginning, we made a lot of attempts based on previous reactions conditions and only detected the carboxylation products. As the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…A series of control experiments revealed that CO 2 , visible light, photocatalyst, reductant, and base were all essential for this transformation (entries 2–6). It is worth mentioning that when either the photocatalyst, reductant, or light was not present, carboxylation occurred at the β‐position to provide 2 a′ in high yields, which was consistent with our previous work . Other photocatalysts, such as fac ‐Ir(ppy) 3 (entry 7), gave lower yields (see the Supporting Information for more details).…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…A series of control experiments revealed that CO 2 , visible light, photocatalyst, reductant, and base were all essential for this transformation (entries 2–6). It is worth mentioning that when either the photocatalyst, reductant, or light was not present, carboxylation occurred at the β‐position to provide 2 a′ in high yields, which was consistent with our previous work . Other photocatalysts, such as fac ‐Ir(ppy) 3 (entry 7), gave lower yields (see the Supporting Information for more details).…”
Section: Methodssupporting
confidence: 90%
“…However, no reports on the hydrocarboxylation of enamides with CO 2 have been realized. Owing to the inherent nucleophilicity at the β‐position, enamides tend to undergo β‐carboxylation with CO 2 smoothly (Scheme 1 B), which is a competitive side reaction and renders the desired umpolung hydrocarboxylation with CO 2 very challenging. Inspired by recent light‐driven organic transformations with CO 2 , we hypothesized that this goal might be achieved through visible‐light‐driven reduction of enamides, which are in equilibrium with imines, to generate α‐amino carbanions I as the key intermediates, and following trapping by CO 2 to give carboxylates II (Scheme C).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, palladium-based materials attracted attention, for example, in the field of microtechnology and can be found, for example, as integrant in gas sensors [1,2], as metal contacts in field-effect transistors [3], or as parts in hydrogen permeable selective membranes [4]. Furthermore, palladium(II) complexes [5][6][7][8][9], palladium nanoparticles [10,11], palladium films [12], or palladium composite materials [13] can be used as active components in homogeneous and heterogeneous catalysis, i.e. C,C cross-coupling [14] and C-H activation reactions [15].…”
Section: Introductionmentioning
confidence: 99%
“… 12 However, there is no report to generate important aryl acetic acids via the cleavage of C N double bonds with a catalytic system. As part of our continuing interest in advancing sustainable organic synthesis with CO 2 , 13 we wondered whether transition metal-catalysis could resolve such a challenge with different reaction mechanisms. Recently, one of us has developed Ru-catalyzed umpolung reactions with carbonyls as carbanion equivalents.…”
Section: Introductionmentioning
confidence: 99%